Factors associated with medical orders’ compliance among hyperlipidemic patients - Dehkordi, Leila Mardanian (Medknow Publications & Meida Pvt Ltd, 2013)
BACKGROUND: Coronary artery diseases are one of the most important issues in health and social problems. One of the amendable risk factors in development of these diseases is high cholesterol which can be modified through correction of lifestyle (diet change, playing sports, and usage of lipid-lowering drugs). Patients’ compliance to therapeutic programs is the most important element to achieve this goal. This study aims to define the factors associated with compliance to medications among hyperlipidemic patients. MATERIALS AND METHODS: This is a descriptive analytical study conducted on 82 hyperlipidemic patients. The data were collected by a questionnaire including two sections: The first section was about demographic characteristics and the second section contained a questionnaire extracted from Foley questionnaire (2005) to inquire medication compliance. The data were analyzed by descriptive statistics (mean), Pearson Spearman correlation coefficients, and independent t-test. RESULTS: Based on the findings, it was evident that most of the hyperlipidemic individuals were compliant. There was a significant association between scores of medication compliance and age (P = 0.035), the number of family members (P = 0.033), the number of consumed drugs (P = 0.022), and education (P < 0.001). CONCLUSION: The results obtained in the present study were consistent with those of other studies reporting high compliance to medication among hyperlipidemic patients and possibly are one of the reasons for the low number of consumed drugs. Since compliance was lower among the individuals with increased age, lesser number of family members, and lesser education, these groups should be supported to promote their level of compliance to medication orders, and this important issue should be included in their educational programs.